2019
DOI: 10.1016/j.microc.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Elemental characterization of surface and bulk of copper-based coins from the Byzantine-period by means of spectroscopic techniques

Abstract: Thirty-three Byzantine copper-based coins (so-called anonymous follis) from 970 to 1085 A.D. were investigated in order to determine the elemental composition both of the bulk and of the surface. The ancient coins analysed − belonging to the Thomas Bertelè Collection, now located in the Bottacin Museum of Padova (Italy) − were studied by way of physical, chemical and chemometric testing techniques. This study aims to obtain information on socio-economic aspects of the Byzantine Empire using chemical and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Conversely, tin is enriched on the surface when it is present in conjunction with zinc, whereas in high-tin bronzes it is usually depleted in the corrosion layer (Gaudenzi Asinelli and Martinón-Torres 2016). Crosera et al (2019) found that Cu was slightly depleted on the surface (91.7 ± 3.1% determined by μXRF analysis) compared to the bulk (95.9 ± 3.1% determined by ICP-AES); however, taking into account their uncertainties, both results actually overlap.…”
Section: Limitations Of Surface Analysis a Literature Reviewmentioning
confidence: 93%
“…Conversely, tin is enriched on the surface when it is present in conjunction with zinc, whereas in high-tin bronzes it is usually depleted in the corrosion layer (Gaudenzi Asinelli and Martinón-Torres 2016). Crosera et al (2019) found that Cu was slightly depleted on the surface (91.7 ± 3.1% determined by μXRF analysis) compared to the bulk (95.9 ± 3.1% determined by ICP-AES); however, taking into account their uncertainties, both results actually overlap.…”
Section: Limitations Of Surface Analysis a Literature Reviewmentioning
confidence: 93%
“…In order to document the cleaning procedure's effect and trace the particularities of the corrosive processes that altered the MMB coins, different analytical methods and measurements were applied. Given the coins' fragility, these methods were required to be sensitive and non-destructive, as is anyway preferable with archaeological objects [26,27]. Our analytical procedure consisted of the following:…”
Section: Methodsmentioning
confidence: 99%
“…This type of patina consists of copper, chlorine and traces of oxygen, aluminium and phosphorous (Figure 8b,c; Table 3) but, unfortunately, it was not identified by Raman spectroscopy. The formation of chlorides on the surface of a buried metal product is due to a humid or saline underground environment [18,73]. The chlorine ion attacks the copper from its oxides or carbonates transforming it into cuprous chloride and for this reason they often stratify on the surface of the coin [74].…”
Section: Chlorides Corrosion Productsmentioning
confidence: 99%
“…The necessary condition to have a reliable investigation is the homogeneity of the surface, which is difficult to have on objects that have been buried for a long time and which must not be further altered by diagnostic analyses. For this reason, a semi-quantitative significance is often assigned to portable X-ray fluorescence (pXRF) surface analyses [18]. Several authors have tried to use the pXRF technique for the chemical analysis of the alloy composition, in part because it consists of portable instrument that can be easily transported into the museums where ancient monetary collections are kept [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%